PELAKSANAAN EKSTRAKURIKULER TARI GALOMBANG DI MTsN 6 SOLOK SELATAN - Alfiyah Zahara; Syeilendra (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to examine the implementation of the Galombang dance extracurricular activities at MTsN 6 Solok Selatan. This research is qualitative in nature with a descriptive method employed. The research instrument is the researcher themselves, assisted by supporting instruments such as writing tools and a camera. Data was collected through literature study, observation, interviews and documentation. The steps for analysing the data are data collection, data analysis and data reduction. The results of the study indicate that the implementation of the Galombang dance extracurricular activities was well-coordinated according to the programme created by the Coach, including the schedule, timing and objectives of the programme. The Galombang dance extracurricular activities were held six times, on Thursdays and Saturdays each week. The implementation of extracurricular activities can run well and strives to be as effective as possible according to the schedule, although there are some challenges with a few students being less disciplined. This, of course, becomes an obstacle in the execution of extracurricular activities, so support from the school is needed to overcome these challenges. In addition, teachers also motivate students so that they are enthusiastic, always present, and energetic at every meeting. Based on the evaluation results, the students' success in each training session continues to improve, and the achievement of training targets is also met. Even after six sessions, students are already able to perform the Galombang dance, which is demonstrated by their performance during the talent and interest show.